Diversidade da composição química dos óleos essenciais de Eugenia – Myrtaceae: uma revisão - Silveira, Raisa Maria (2021)
Myrtaceae is a pantropical family with approximately 132 genera and 5.760 species. In the family, essential oils are widely produced by their representatives, to the point that the presence of their secretory structures are used in taxonomic identification. This is the case of the species of Eugenia, the largest neotropical genus of Myrtaceae, comprising more than 1000 species. The aim of the present work was to carry out a wide bibliographic review of published research on the chemical composition of essential oils of Eugenia species. The methodology used was to carry out bibliographic research on the specialized sites of scientific journals using the terms 'Myrtaceae', 'Eugenia' 'Essential Oils', 'Chemical composition' between february and december 2019. The results were organized in a table, containing the compiled data of the chemical composition of essential oils of 78 species of Eugenia, present in 139 scientific studies and 317 records of essential oils for different species. The studies on the chemical composition of the essential essentials of Eugenia are numerous, however, they are concentrated on a few species of the genus.